Diagnosis and management of acromegaly: the patient's perspective - Kreitschmann-Andermahr, Ilonka; Siegel, Sonja; Kleist, Bernadette; Kohlmann, Johannes; Starz, Daniel; Buslei, Rolf; Koltowska-Haggstrom, Maria; Strasburger, Christian J.; Buchfelder, Michael (Pituitary, 2016)
Early diagnosis is a success factor for the prevention of long-term comorbidity and premature death in patients with acromegaly, but large-scale data on the diagnostic process and disease management are scarce. Therefore, we aimed to evaluate the diagnostic process, implementation of treatment and changes in life situation in patients with acromegaly, focusing on sex-specific differences.Non-interventional patient-reported outcome study. 165 patients with clinically and biochemically proven acromegaly were questioned about the diagnostic process and utilization of health care by means of a self-developed standardized postal survey including questions on acromegaly symptoms experienced before diagnosis, number and specialty of consulted doctors, time to diagnosis and aftercare.The diagnostic process took 2.9 (SD 4.53) years, during which 3.4 (SD 2.99) physicians were consulted. Women waited longer [4.1 (SD 5.53) years] than men [1.6 (SD 2.69) years; p = 0.001] for the correct diagnosis, and consulted more doctors in the process [4.0 (SD 2.99) vs. 2.7 (SD 2.84) doctors, p < 0.001, respectively]. In 48.5 % of patients, acromegaly was diagnosed by an endocrinologist (men: 45.1 %; women: 52.4 %). Overall disease duration from symptom onset until last surgery was 5.5 (SD 6.85) years, with no sex differences. A change in employment status was the most commonly reported event after diagnosis and a quarter of the patients stated that the illness had changed their lives.Our findings confirm the urgent need to increase awareness of the clinical manifestation of acromegaly to facilitate an earlier diagnosis of the disease and to provide diagnostic equality across the sexes.
EVALuna2:7322

From first symptoms to final diagnosis of Cushing's disease: experiences of 176 patients - Kreitschmann-Andermahr, Ilonka; Psaras, Tsambika; Tsiogka, Maria; Starz, Daniel; Kleist, Bernadette; Siegel, Sonja; Milian, Monika; Kohlmann, Johannes; Menzel, Christa; Fuehrer-Sakel, Dagmar; Honegger, Juergen; Sure, Ulrich; et al. (European Journal of Endocrinology, 2015)
To obtain structured information on the diagnostic delay in patients with Cushing's disease (CD) from the patients perspective to provide leverage points for earlier diagnosis.The study includes 176 patients with ACTH-dependent CD who had received pituitary surgery completed a self-developed questionnaire on their symptomatology before the illness was diagnosed, the course and length of the diagnostic process, and the role of the involved health care professionals.Data were analyzed statistically. Answers in free text options were categorized and counted.The overall diagnostic process took 3.8±4.8 years (median 2 years), during which 4.6±3.8 (1-30) physicians were consulted, most frequently the family physician (FP; 83.0%). The presented symptoms were various and often vague, e.g. 'poor general condition' (at FPs), or very common in the field of the visited specialist (i.e. 'skin changes' at dermatologists). Women recognized the first CD symptoms themselves significantly more frequently than men, whereas physicians recognized CD symptoms significantly more frequently in males.A clear difficulty of diagnosing CD seems that patients describe isolated symptoms to the FP or the respective specialists according to their fields of specialization. As FPs are contacted most frequently, they should be trained to recognize the broad spectrum of CD symptoms, especially in female patients with weight gain, and initiate endocrinological referral.
EVALuna2:22869